2004
DOI: 10.1289/txg.6861
|View full text |Cite
|
Sign up to set email alerts
|

Toxicogenomics of Subchronic Hexachlorobenzene Exposure in Brown Norway Rats

Abstract: ) for performing the radioimmunoassay to determine antiacetylcholine receptor antibodies, and we thank B. Baumann (RIVM, Bilthoven, the Netherlands) for measuring the dioxin-like contamination of HCB.The authors declare they have no competing financial interests.Received 13 Hexachlorobenzene (HCB) is a persistent environmental pollutant with toxic effects in man and rat. Reported adverse effects are hepatic porphyria, neurotoxicity, and adverse effects on the reproductive and immune system. To obtain more ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…The prospects are that gene expression studies will enable a fast and sensitive detection and evaluation of environmental stressors and toxicants. This is strengthened by the fact that several recent studies have shown that transcription profiling can be applied as an early indicator of toxicity [ 10 , 11 ] in a dose-dependent manner [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The prospects are that gene expression studies will enable a fast and sensitive detection and evaluation of environmental stressors and toxicants. This is strengthened by the fact that several recent studies have shown that transcription profiling can be applied as an early indicator of toxicity [ 10 , 11 ] in a dose-dependent manner [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The enriched genes also included many genes related to the inflammatory response, including IL‐2 and IL‐6, thus suggesting that HCB may also induce inflammation. Ezendam et al observed that HCB could induce systemic inflammation (testicular inflammation was not specifically investigated in their study), which was accompanied by oxidative stress and acute‐phase reactions (Ezendam et al., 2004). Overall, our results suggest that oxidative stress is involved in HCG‐induced damage to the testis and that the inflammatory response may also play a role in this process.…”
Section: Discussionmentioning
confidence: 96%
“…The excessive accumulation of ROS can lead to cell apoptosis, lipid peroxidation and mitochondrial dysfunction (Badgley et al., 2020; Ozawa et al., 2020; Yang & Kim, 2018). Studies have shown that HCB can increase the content of ROS and induce oxidative stress (Addae et al., 2013; Ezendam et al., 2004). For example, after rats were administered with HCB, there was a significant increase in liver lipid peroxidation and glutathione (GSH) content, while the activities of antioxidant enzymes, such as SOD and CAT, were significantly reduced.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations